ANALISIS KERENTANAN PENGHIDUPAN RUMAH TANGGA TANI AKIBAT PERUBAHAN IKLIM DI KABUPATEN GUNUNGKIDUL - Arief Wahyu Widada (Agro Ekonomi, 2014)
This research is aim at knowing farmer’s household knowledge to climate change in sub urban and rural area, knowing the farmer’s household is affected by exposure of climate change in sub urban and rural area, knowing adaptive strategy of farmer’s household to climate change in sub urban and rural area, and calculating the Livelihood Vulnerability Index (LVI) of farmer’s household to climate change in sub urban and rural area. This research was done in Gunungkidul Regency by purposive included sub urban and rural area.  There was 60 respondents of farmer’s household token by random sampling method and chose every 30 respondents in each area. This research used descriptive table analysis method and index calculation. The results of this research show that farmer’s household in sub urban and rural area of Gunungkidul Regency have low knowledge to climate change. The farmer’s household in sub urban and rural area of Gunungkidul Regency feels the rain more uncertainly and more difficult to determine the beginning of planting season. The farmer’s household in sub urban area is feels more climate change impact. The farmer’s household in sub urban area has more farming adaptive strategy to climate change. The farmer’s household in sub urban area is more expose and more sensitive to climate change but has more adaptive capacity to climate change. The farmer’s household in sub urban area is more vulnerable in climate change than rural area in both of LVI and LVI-IPCC calculation method.